THE EFFECTIVENESS OF USING VISUAL EXERCISES ON LEARNING SOME FOOTBALL SKILLS FOR DEAF AND DUMB PLAYERS (12-14 YEARS) - Maytham Mohsin Habeeb; Munadhil Adil Kiasm (American Journals Publishing, 2025)
Skills for deaf and dumb players aged 12 to 14 years. The inadequate performance in this category arises from insufficient mastery and consistency in skill execution, negatively impacting skill competency, a shortcoming that may endure into later stages of life. The researchers utilised an experimental methodology on a sample of 20 players, comprising an experimental group of 10 players and a control group of 8 players. The execution of a training program focused on visual exercises and diverse skill assessments in football revealed that such exercises improved the football skills of deaf and dumb participants in the study. Statistically significant differences are present in the football skill test findings within the research sample, with the experimental group exhibiting superiority over the control group in the evaluated football skills.
Keywords: Curriculum, visual exercise, skills, football, deaf and dumb.